Porovnání přesnosti spektroskopických a zobrazovacích technik magnetické rezonance pro stanovení jaterní steatózy - Šedivý, Petr; Dezortová, Monika; Burian, Martin; Dusilová, Tereza; Kovář, Jan; Hájek, Milan (Chemické listy, 2021)
The article describes the determination of the amount of fat in liver tissue (steatosis) by non-invasive methods of 1H magnetic resonance (MR) spectroscopy and MR imaging in vivo on whole body tomographs. Commercially available PRESS, STEAM and HISTO techniques for 1H MR spectroscopy and 3D-Dixon techniques for MR imaging on a 3T MR tomograph were used. The accuracy and usability of individual techniques were verified on prepared lipid phantoms in the concentration range of 2.5–30% fat and on a representative group of volunteers. It turns out that MR spectroscopic and imaging methods are currently fully comparable.